(untitled) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2025)
Arcus senilis is a well-recognized clinical sign frequently encountered in the elderly population, characterized by an opaque, grayish white ring or arc visible at the peripheral cornea. This corneal manifestation is not merely an isolated ophthalmic finding; rather, it can be intricately linked to systemic conditions, notably cardiovascular diseases. Understanding the morphological and clinical features of arcus senilis, and correlating them with the complications of cardiovascular pathologies is pivotal for timely diagnosis, patient education, and the development of effective preventive strategies.